2015
DOI: 10.1112/plms/pdv012
|View full text |Cite
|
Sign up to set email alerts
|

Computing topological zeta functions of groups, algebras, and modules, I

Abstract: We develop techniques for computing zeta functions associated with nilpotent groups, not necessarily associative algebras, and modules, as well as Igusa‐type zeta functions. At the heart of our method lies an explicit convex‐geometric formula for a class of p‐adic integrals under non‐degeneracy conditions with respect to associated Newton polytopes. Our techniques prove to be especially useful for the computation of topological zeta functions associated with algebras, resulting in the first systematic investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(88 citation statements)
references
References 50 publications
(138 reference statements)
0
88
0
Order By: Relevance
“…Then, it is necessary to show that definition (4.1) is independent of the resolution of singularities chosen, this fact was established by Denef and Loeser in [31], see also [32]. By using the explicit formula (B.5)-(B.6), Denef and Loeser showed that…”
Section: Jhep08(2018)043mentioning
confidence: 99%
See 2 more Smart Citations
“…Then, it is necessary to show that definition (4.1) is independent of the resolution of singularities chosen, this fact was established by Denef and Loeser in [31], see also [32]. By using the explicit formula (B.5)-(B.6), Denef and Loeser showed that…”
Section: Jhep08(2018)043mentioning
confidence: 99%
“…Section 4 gives the description of the p → 1 limit of the p-adic string amplitudes. For this we use the formulation of topological zeta functions [31,32]. We also present the computation of N = 4 and N = 5 points Denef-Loeser amplitudes.…”
Section: Jhep08(2018)043mentioning
confidence: 99%
See 1 more Smart Citation
“…Informally, the topological ask zeta function ζM top false(sfalse)Qfalse(sfalse) of M is the constant term of false(1qv1false)ζMvfalse(sfalse) as a series in qv1; for a rigorous definition, combine the formalism developed in [, § 5] (and summarised in [, § 4.2]), Proposition and [, proof of Lemma 3.4]. For example, Proposition implies that ζprefixMd×efalse(boldZfalse) top false(sfalse)=s+es(sd+e).We note that, as in the case of subobject [, Proposition 5.19] and representation zeta functions [, Proposition 4.3], the topological ask zeta function of M only depends on Mfrakturok¯, where truek¯ is an algebraic closure of k.…”
Section: Rationality Of Sans-serifzmfalse(tfalse) and P‐adic Integrationmentioning
confidence: 99%
“…Supposing that Question indeed has a positive answer, if GprefixUdboldZk is an algebraic group over k with associated frakturo‐form GprefixUdboldZo (see Corollary ), then we may evaluate the meromorphic continuation of sans-serifZG(frakturov)sans-serifocfalse(qvsfalse) at s=0 for almost all vscriptVk. Inspired by similar questions regarding the behaviour at zero of local subalgebra [, Conjecture IV], submodule [, Conjecture E] and representation [, Question 8.5] zeta functions, it would then be interesting to see if one can interpret the resulting rational numbers, say in terms of properties of the orbit space frakturovd/Gfalse(ovfalse).…”
Section: Further Examplesmentioning
confidence: 99%